(untitled) (Research, Society and Development, 2022)
Mass incarceration is a growing movement in Brazil that affects the female population as well. Women imprisonment nowadays reads mountain-high rates, drug related crimes being the main reason for this scenario, once that they make up 56.16% of women under the custody of penitentiary systems in the country. Thus, this assignment’s general objective is to analyse the characteristics of Brazilian scientific papers about the inclusion and partaking of women in drug trafficking. In order to achieve this, it has been applied the method of systematic literature review, ruled in the process of gathering, critical evaluation and synthesis of multiple studies’s results. After all analyses were met, it has been concluded that the number of papers surrounding the subject is embryonic, hence requiring the development of further, increasingly in-depth, studies aimed at the investigation of relationships between scientific funding, authoring and quality.